Selección de hábitat por el venado cola blanca Odocoileus virginianus mexicanus (Gmelin, 1788) y su densidad poblacional en dos localidades de la región centro del Corredor Biológico Chichinautzin, Morelos, México. - Flores-Armillas, Víctor Hugo; Gallina, Sonia; García Barrios, José Raúl; Sánchez-Cordero, Víctor; Jaramillo Monrroy, Fernando (THERYA, 2011)
In the Natural Protected Corridor Chichinautzin (CBCH) there are issues such as hunting, deforestation, expansion of the agricultural frontier, urbanization and poor planning in natural resource management. The management of deer species has been shown to have great potential to promote conservation and sustainable use of the ecosystem of which they form part of. Before proposing a management strategy for white-tailed deer in the CBCH, it is necessary to consider the basic characteristics of the species distribution in the area, obtain reliable data on their population density and set policies consistent with management information obtained. This study is an important contribution to the knowledge of the species in temperate forests of the state of Morelos, since there was no record of habitat use and population density. Population density was obtained within the scope of 2.74 Â± 3.62 deer/km2 in the town of the San Juan Tlacotenco and 2.71 Â± 2.07 deer/km2 in the Huexcalapa volcano, wich is considered low relative to other investigations with the same species in the same type of habitat. On the other hand, in terms of habitat selection, white-tailed deer preferred the pine-oak forest and cloud forest. The low density of white-tailed deer appears to be related to a set of factors such as land use change, poaching and habitat availability.